2001
DOI: 10.1002/hed.1106
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cervical node involvement in metastatic cutaneous malignancy involving the parotid gland

Abstract: Patients with metastatic cutaneous SCC and melanoma involving the parotid gland had a high incidence of clinical (26% and 38%, respectively) and occult neck disease (35% and 27%). Treatment of the clinically negative neck in the presence of clinical metastatic parotid cancer should be considered to reduce the likelihood of failure in cervical nodes, to define the extent of disease, and to assist with patient selection for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(35 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…Although the clinical findings portend the neck as a principal metastatic site, the possibility of clinically occult parotid metastatic disease must not be discarded and surgery extent should be planned accordingly, as was previously discussed in a study by O'Brien et al 11 Previous studies have shown that parotid metastatic involvement leads to a poorer prognosis when compared to patients that had regional metastatic disease in the neck alone, with the parotid gland free from disease. 21,23 Our results indicate that for patients with clinically positive parotid involvement and occult neck metastatic disease, an elective neck dissection might be beneficial without significant increase in surgery related comorbidity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although the clinical findings portend the neck as a principal metastatic site, the possibility of clinically occult parotid metastatic disease must not be discarded and surgery extent should be planned accordingly, as was previously discussed in a study by O'Brien et al 11 Previous studies have shown that parotid metastatic involvement leads to a poorer prognosis when compared to patients that had regional metastatic disease in the neck alone, with the parotid gland free from disease. 21,23 Our results indicate that for patients with clinically positive parotid involvement and occult neck metastatic disease, an elective neck dissection might be beneficial without significant increase in surgery related comorbidity.…”
Section: Discussionmentioning
confidence: 74%
“…Similar results confirm this finding. 1,11,12,16,21,23 Clinically evident metastatic neck disease staged by the PN system shows a statistically significant correlation with survival rate. The N1 group had the best outcome, while N2 had the worst outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Th ey are: superfi cial spreading melanoma (SSM), which occurs in about 70% of patients; nodular malignant melanoma (NM), which occurs in about 15% of patients; and lentigo maligna melanoma (LMM), which occurs in about 15%, in older patients, on the exposed parts of the body on the basis of premalignant melanosis as the result of chronic exposure to sunlight; according to the personal clinical experience of Professor Virag, acral melanomas do not occur on the skin of the head and neck 5 . Melanomas of the skin are located in the area of the face and the front of the hair, accounting for most melanomas of the face and neck, and are related to lymph nodes in the parotid region 6 . In the superfi cial lobe of the parotid gland, there are 2 to 10 lymph nodes, but half as many nodes lie medially to the facial nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Si existen metástasis ganglionares parotídeas debe realizarse, además de la parotidectomía correspondiente, una disección cervical, por la elevada probabilidad de presentar metástasis en los ganglios linfáticos cervicales (entre el 47% y el 58%). 19 Por el contrario, en los pacientes con enfermedad localizada (N0) el beneficio de las disecciones profilácticas sobre la supervivencia global continúa siendo uno de los aspectos más controvertidos. La linfadenectomía profiláctica persigue erradicar las micrometástasis ganglionares y aumentar así el porcentaje de curación.…”
Section: Ganglios Centinelasunclassified
“…7,10,11 carried out as well as the corresponding parotidectomy, as there is a high probability of there being metastasis in the cervical lymph nodes (between 47% and 58%). 19 On the contrary, with patients with localized disease (N0) the advantages of prophylactic dissection on the global survival continues being one of the more controversial aspects. Prophylactic lymphadenctomy is aimed at eradicating micrometastatic lymph nodes in order to increase the cure rate.…”
Section: Ganglios Centinelasmentioning
confidence: 99%